VARIANTS TEXT DARMASONYA - A Aryanto; B Sudardi; A Purwasito; W Abdullah (Universitas Sebelas Maret, 2017)
The manuscript by the name of Darmasonya in the literary knowledge of Javanese literature can be regarded as one of the popular texts. The popularity of this Darmasonya script can be seen from its first appearance in ancient Javanese times until the early Surakarta period. This is quite interesting considering the time of the emergence of the script of Ancient Javanese Darmasonya with the script of the Darmasonya of the Surakarta era The beginning of which is too far away. Darmasonya name is still used in early Surakarta. The manuscript under the name Darmasonya has existed since ancient Javanese times in the form of a rontal script (lontar) kakawin dharma sunya. Manuscript kakawin dharma sunya has several variants such as kakawin dharma sunyakling and kakawin dharma putus. However, it is possible to find other variants of kakawin dharma sunya. Then, Darmasonya script in Surakarta era Early in the form of tembang macapat and prose (gancaran). So, this study focuses on the variants of Darmasonya text by way of tracking seen from the side of the same name, namely Darmasonya.